Longitudinal investigation of neurobiological changes across pregnancy - Yanbin Niu; Benjamin N. Conrad; M. Catalina Camacho; Sanjana Ravi; Hannah A. Piersiak; Lauren G. Bailes; Whitney Barnett; Mary Kate Manhard; David A. Cole; Ellen Wright Clayton; Sarah S. Osmundson; Seth A. Smith; et al. (Communications Biology)
Abstract Pregnancy is a period of profound biological transformation. However, we know remarkably little about pregnancy-related brain changes. To address this gap, we chart longitudinal changes in brain structure during pregnancy and explore potential mechanisms driving these changes. Ten participants (Mean age = 28.97 years) are assessed 1–6 times (median = 3) during their pregnancy. Each visit includes anatomical and diffusion-weighted MRI, and assessments of waking salivary hormones, hair hormones, and inflammatory cytokines. Here we observe a reduction in gray matter volume and an increase in neurite density index (NDI), a proxy of axon density, in white matter tracts across pregnancy. Progesterone levels are associated with reductions in brain volumetric measurements, and both progesterone and estradiol levels are linked to increases in NDI in white matter tracts. This study highlights the profound neurobiological changes experienced by pregnant individuals and provides insights into neuroplasticity in adulthood.